Trash-Talking Pemain Mobile Legends: Bang Bang Mahasiswa FKIP UNS - Mia Ambarwati; Nurhadi; Abdul Rahman (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
In this digital era, the development of online games in the world is increasing. The most popular online game in Indonesia is Mobile Legends: Bang Bang. One of the things that stands out in the game Mobile Legends: Bang Bang is the occurrence of trash-talking behavior. The purpose of this study is to find out the meaning of trash-talking players in Mobile Legends: Bang Bang. The method used is descriptive qualitative research method. The research data were collected using the participant observation method. The data sources in this study were 5 participants, determined using a purposive sampling technique with the criteria that FKIP UNS students were actively playing the online game Mobile Legends: Bang Bang. The data analysis technique in this study used the equivalent method. The results showed that the type of trash-talking was divided into four categories, namely the category of intelligence/intelligence including: pekok, tolol, noob, goblok, beleguk, kehed and pe’ak. Sexuality categories include: lee, sangean, ngentot and pepek. The category of disgusting animals is in the form of animal names such as: babi, asu and anjing. The general categories are cuk, lol, fuck, dancok, najis, bangsat, modar, bajingan and bacot. The meaning of trash-talking seen from the situation that occurs is divided into two, namely positive and negative meanings. Positive meaning occurs when trash-talking presents a pleasant situation such as breaking the atmosphere, as a symbol of intimacy, giving a humorous effect and motivating players. The negative meanings occur when trash-talking presents toxic behavior such as annoyance, anxiety, expressions of anger, humiliation and disappointment of the players. Trash-talking in the online game Mobile Legends: Bang Bang is a form of cultural expression as part of local wisdom that characterizes the players' regions of origin.